2021
DOI: 10.1101/2021.04.01.437998
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-Cell Multiomics Reveals Distinct Cell States at the Top of the Human Hematopoietic Hierarchy

Abstract: The advent of single cell (Sc) genomics has challenged the dogma of haematopoiesis as a tree-like structure of stepwise lineage commitment through distinct and increasingly restricted progenitor populations. Instead, analysis of ScRNA-seq has proposed that the earliest events in human hematopoietic stem cell (HSC) differentiation are characterized by only subtle molecular changes, with hematopoietic stem and progenitor cells (HSPCs) existing as a continuum of low-primed cell-states that gradually transition in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 49 publications
5
37
1
Order By: Relevance
“…This also applies for the lymphoid surface markers, where CD10, mainly captured the lympho-myeloid cluster Ly-I, whereas our data revealed that IL7R in combination with CD38 and CD45RA could capture the Ly-II cell state with high purity in the embryo. This was opposite as to what was seen in adult where the population captured by CD10 comprised 70% Ly-II cells vs 43% when using IL7R ( data not shown and (Sommarin et al, 2021)). Thus, CITE-seq detects molecular heterogeneity within immunophenotypic progenitors, but also identifies surface markers that are preserved throughout development.…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…This also applies for the lymphoid surface markers, where CD10, mainly captured the lympho-myeloid cluster Ly-I, whereas our data revealed that IL7R in combination with CD38 and CD45RA could capture the Ly-II cell state with high purity in the embryo. This was opposite as to what was seen in adult where the population captured by CD10 comprised 70% Ly-II cells vs 43% when using IL7R ( data not shown and (Sommarin et al, 2021)). Thus, CITE-seq detects molecular heterogeneity within immunophenotypic progenitors, but also identifies surface markers that are preserved throughout development.…”
Section: Discussioncontrasting
confidence: 68%
“…Next, the fetal cells were directly compared with our adult BM data set of HSPCs, analyzed with CITE-seq in a similar way and using the same platform as the fetal cells (Sommarin et al, 2021) ( Figure 3a and Sup Figure 2a ). First, the pseudo-bulked immunophenotypic gated populations from fetal and adult were compared using PCA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations